2020
DOI: 10.1177/1098612x20942382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a struvite dissolution diet in cats with naturally occurring struvite urolithiasis

Abstract: Objectives The aim of the study was to determine the efficacy of the low struvite relative supersaturation diet in dissolution of feline struvite cystoliths. Methods This was a prospective, open-label, two-center study. Twelve client-owned cats were enrolled based on the radiographic appearance of their uroliths and urinalysis parameters. Cats were fed the test diet exclusively for up to 56 days. Cats were radiographed every other week until radiographic evidence of dissolution occurred or the end of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…The low proportion of positive struvite-containing urolith cultures is similar to a prior study 6 and consistent with this mineral type most often being sterile in cats rather than infection-associated, as typically noted in dogs. 6,19 Because the most common bacteria cultured were Staphylococcus spp., struvitecontaining uroliths in cats can be infection-associated. Interpretation of urolith cultures should be tailored to the individual patient and antimicrobials often are not warranted if clinical signs are no longer present after the urolith is removed.…”
Section: Urolith Bacterial Culture Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low proportion of positive struvite-containing urolith cultures is similar to a prior study 6 and consistent with this mineral type most often being sterile in cats rather than infection-associated, as typically noted in dogs. 6,19 Because the most common bacteria cultured were Staphylococcus spp., struvitecontaining uroliths in cats can be infection-associated. Interpretation of urolith cultures should be tailored to the individual patient and antimicrobials often are not warranted if clinical signs are no longer present after the urolith is removed.…”
Section: Urolith Bacterial Culture Resultsmentioning
confidence: 99%
“…Moreover, studies evaluating struvite dissolution protocols in cats reported no apatite mineral content in the uroliths from the majority of nonresponders; apatite content in responders cannot be evaluated. [17][18][19] Our data suggest that further education regarding noninvasive treatment for suspected struvite urolithiasis is needed to promote dietary dissolution as the first therapeutic approach. 21 If dietary treatment fails, urolith removal and accurate histories should help elucidate reasons for failure.…”
Section: Urolith Bacterial Culture Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, controlling intake, and thus, to a degree, excretion of precursor minerals can reduce the substrate for crystal formation (30). The contribution of urinary protein to struvite crystalluria has been less commonly reported but demonstrated in vitro, making consideration of dietary protein levels warranted to reduce protein excretion (31).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ammonia and a pH > 6.0 are required for precipitation to occur, as high urinary pH reduces the solubility of phosphorus and magnesium in the urine, allowing the ammonia to bind the minerals leading to precipitation as struvite crystals (29,31). Manipulation of the urinary pH to maintain a slightly acidic (pH < 6.5) environment thus increases solubility of struvite, reducing crystal precipitation (30,32). Urine pH can be manipulated by inclusion of acidic sulfur-containing amino acids and minerals such as phosphorus, chloride and sulfur, and restriction of basic minerals, such as calcium, magnesium, sodium, and potassium.…”
Section: Discussionmentioning
confidence: 99%